The shorter science and civilisation in China (Cambridge University Press)
1. 1980. - IX, 326 p. : ill. ; 22 cm. - First publ. in 1978. - Abridgement of volumes I and II of the major series. - Bibl., index. - ISBN 0-521-29286-7. - ISBN 0-521-21821-7